THE ROLE OF SOCIAL CAPITAL IN THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR): LESSON LEARNED FROM PT. UNILEVER INDONESIA TBK - Kartika Dewi Sri Susilowati (Faculty of Economics and Business, University of Muhammadiyah Malang, 2017)
This study was conducted to provide an overview on how the multi-stakeholders partnership model on the Black Soybeans Project capable of creating economic value to all parties involved in the project. This paper focuses strongly on the role of social capital in multi-stakeholders partnership model which was developed by PT. Unilever Indonesia Tbk in the implementation of corporate social responsibility in Bantul, Yogyakarta. In this research context social capital is defined as the networks, trust, norms and commitment that enable Unilever and its stakeholders to achieve mutual defined goals through collaboration. This is a post-positivist paradigm phenomenology-interpretive research. Data were collected by conducting in-depth interviews with key informants involved in the project e.g. university’s academicians, NGO, financial institutions, farmers, women/wives of farmers and Unilever of Indonesia Foundation. The study shows that the partnership was created based on the principle of symbiosis-mutualism, where each partner gets some benefits from its partnership. The partnership was developed to empower black soy beans farmers to provide a guarantee supply of black soybeans with a quantity, quality and price in accordance with the standards established by the Unilever. In cooperation with various stakeholders, Unilever has developed some production centers of black soybeans to fulfill it needs. By doing this, the company is able to improve the quality of life of the farmers. Therefore, this project has fulfilled two different values: economics (business) value and social value.